Lightning-Warning Systems for Use by Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s Airport Cooperative Research Program (ACRP) Report 8: Lightning-Warning Systems for Use by Airports explores the operational benefits associated with delay reductions that lightning detection and warning systems may be able to generate. The report is designed to help in the assessment of whether such systems are cost-beneficial on an individual airport or airline basis.An ACRP Impacts on Practice related to ACRP Report 8 was produced in 2011.
Keywords: Transportation and Infrastructure

Selection and Application of Warning Lights on Roadway Operations Equipment - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB's National Cooperative Highway Research Program (NCHRP) Report 624: Selection and Application of Warning Lights on Roadway Operations Equipment explores recommended guidelines for the selection and application of warning lights on roadway operations equipment.Appendixes A through E to NCHRP Report 624 are available online. The appendixes contain detailed information on relevant literature, the experiments performed, and data analysis associated with NCHRP Report 624.
Keywords: Transportation and Infrastructure

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2007 Symposium - National Academy of Engineering (The National Academies Press, 2008)
U.S. Frontiers of Engineering (USFOE) symposia bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2007 symposium covered engineering trustworthy computer systems, control of protein conformations, biotechnology for fuels and chemicals, modulating and simulating human behavior, and safe water technologies. Papers in this volume describe leading-edge research on disparate tools in software security, decoding the "mechanome," corn-based materials, modeling human cultural behavior, water treatment by UV irradiation, and many other topics. A speech by dinner speaker Dr. Henrique (Rico) Malvar, managing director of Microsoft Research, is also included. Appendixes provide information about contributors, the symposium program, summaries of break-out sessions, and a list of participants. This is the thirteenth volume in the USFOE series.
Keywords: Engineering and Technology

Changing the Conversation: Messages for Improving Public Understanding of Engineering - National Academy of Engineering (The National Academies Press, 2008)
Can the United States continue to lead the world in innovation? The answer may hinge in part on how well the public understands engineering, a key component of the 'innovation engine'. A related concern is how to encourage young people--particularly girls and under-represented minorities--to consider engineering as a career option. Changing the Conversation provides actionable strategies and market-tested messages for presenting a richer, more positive image of engineering. This book presents and discusses in detail market research about what the public finds most appealing about engineering--as well as what turns the public off. Changing the Conversation is a vital tool for improving the public image of engineering and outreach efforts related to engineering. It will be used by engineers in professional and academic settings including informal learning environments (such as museums and science centers), engineering schools, national engineering societies, technology-based corporations that support education and other outreach to schools and communities, and federal and state agencies and labs that do or promote engineering, technology, and science.
Keywords: Education; Engineering and Technology

Rebuilding the Research Capacity at HUD - National Research Council (The National Academies Press, 2008)
Today, the nation faces an array of housing and urban policy challenges. No federal department other than HUD focuses explicitly on the well-being of urban places or on the spatial relationships among people and economic activities in urban areas. If HUD, Congress, mayors, and other policy makers are to respond effectively to urban issues, they need a much more robust and effective Office of Policy Development and Research (PD&R). PD&R conducts independent research and program evaluation, funds data collection and research by outside organizations, and provides policy advice to the Secretary and to other offices in HUD. Most of PD&R's work is of high quality, relevant, timely, and useful. With adequate resources, PD&R could lead the nation's ongoing process of learning, debate, and experimentation about critical housing and urban development challenges. Rebuilding the Research Capacity at HUD makes seven major recommendations about PD&R's resources and responsibilities, including more active engagement with policy makers, formalizing various informal practices, strengthening surveys and data sets, and more. Acknowledging that the current level of funding for PD&R is inadequate, the book also makes several additional recommendations to help enable PD&R to reach its full potential.
Keywords: Engineering and Technology; Transportation and Infrastructure

Retooling for an Aging America: Building the Health Care Workforce - Institute of Medicine (The National Academies Press, 2008)
As the first of the nation's 78 million baby boomers begin reaching age 65 in 2011, they will face a health care workforce that is too small and woefully unprepared to meet their specific health needs. Retooling for an Aging America calls for bold initiatives starting immediately to train all health care providers in the basics of geriatric care and to prepare family members and other informal caregivers, who currently receive little or no training in how to tend to their aging loved ones. The book also recommends that Medicare, Medicaid, and other health plans pay higher rates to boost recruitment and retention of geriatric specialists and care aides. Educators and health professional groups can use Retooling for an Aging America to institute or increase formal education and training in geriatrics. Consumer groups can use the book to advocate for improving the care for older adults. Health care professional and occupational groups can use it to improve the quality of health care jobs.
Keywords: Health and Medicine; Industry and Labor

Ready, Set, SCIENCE!: Putting Research to Work in K-8 Science Classrooms - National Research Council (The National Academies Press, 2008)
What types of instructional experiences help K-8 students learn science with understanding? What do science educators, teachers, teacher leaders, science specialists, professional development staff, curriculum designers, and school administrators need to know to create and support such experiences? Ready, Set, Science! guides the way with an account of the groundbreaking and comprehensive synthesis of research into teaching and learning science in kindergarten through eighth grade. Based on the recently released National Research Council report Taking Science to School: Learning and Teaching Science in Grades K-8, this book summarizes a rich body of findings from the learning sciences and builds detailed cases of science educators at work to make the implications of research clear, accessible, and stimulating for a broad range of science educators. Ready, Set, Science! is filled with classroom case studies that bring to life the research findings and help readers to replicate success. Most of these stories are based on real classroom experiences that illustrate the complexities that teachers grapple with every day. They show how teachers work to select and design rigorous and engaging instructional tasks, manage classrooms, orchestrate productive discussions with culturally and linguistically diverse groups of students, and help students make their thinking visible using a variety of representational tools. This book will be an essential resource for science education practitioners and contains information that will be extremely useful to everyone ï¿½including parents ï¿½directly or indirectly involved in the teaching of science.
Keywords: Education

Improving Democracy Assistance: Building Knowledge Through Evaluations and Research - National Research Council (The National Academies Press, 2008)
Over the past 25 years, the United States has made support for the spread of democracy to other nations an increasingly important element of its national security policy. These efforts have created a growing demand to find the most effective means to assist in building and strengthening democratic governance under varied conditions. Since 1990, the U.S. Agency for International Development (USAID) has supported democracy and governance (DG) programs in approximately 120 countries and territories, spending an estimated total of $8.47 billion (in constant 2000 U.S. dollars) between 1990 and 2005. Despite these substantial expenditures, our understanding of the actual impacts of USAID DG assistance on progress toward democracy remains limited—and is the subject of much current debate in the policy and scholarly communities. This book, by the National Research Council, provides a roadmap to enable USAID and its partners to assess what works and what does not, both retrospectively and in the future through improved monitoring and evaluation methods and rebuilding USAID's internal capacity to build, absorb, and act on improved knowledge.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Early Childhood Assessment: Why, What, and How - National Research Council (The National Academies Press, 2008)
The assessment of young children's development and learning has recently taken on new importance. Private and government organizations are developing programs to enhance the school readiness of all young children, especially children from economically disadvantaged homes and communities and children with special needs. Well-planned and effective assessment can inform teaching and program improvement, and contribute to better outcomes for children. This book affirms that assessments can make crucial contributions to the improvement of children's well-being, but only if they are well designed, implemented effectively, developed in the context of systematic planning, and are interpreted and used appropriately. Otherwise, assessment of children and programs can have negative consequences for both. The value of assessments therefore requires fundamental attention to their purpose and the design of the larger systems in which they are used. Early Childhood Assessment addresses these issues by identifying the important outcomes for children from birth to age 5 and the quality and purposes of different techniques and instruments for developmental assessments.
Keywords: Behavioral and Social Sciences; Education

Evidence-Based Medicine and the Changing Nature of Health Care: 2007 IOM Annual Meeting Summary - Institute of Medicine (The National Academies Press, 2008)
Drawing on the work of the Roundtable on Evidence-Based Medicine, the 2007 IOM Annual Meeting assessed some of the rapidly occurring changes in health care related to new diagnostic and treatment tools, emerging genetic insights, the developments in information technology, and healthcare costs, and discussed the need for a stronger focus on evidence to ensure that the promise of scientific discovery and technological innovation is efficiently captured to provide the right care for the right patient at the right time. As new discoveries continue to expand the universe of medical interventions, treatments, and methods of care, the need for a more systematic approach to evidence development and application becomes increasingly critical. Without better information about the effectiveness of different treatment options, the resulting uncertainty can lead to the delivery of services that may be unnecessary, unproven, or even harmful. Improving the evidence-base for medicine holds great potential to increase the quality and efficiency of medical care. The Annual Meeting, held on October 8, 2007, brought together many of the nation's leading authorities on various aspects of the issues - both challenges and opportunities - to present their perspectives and engage in discussion with the IOM membership.
Keywords: Health and Medicine

Assessing Accomplished Teaching: Advanced-Level Certification Programs - National Research Council (The National Academies Press, 2008)
The mission of the National Board for Professional Teaching Standards (NBPTS) is to establish "high and rigorous standards for what teachers should know and be able to do, to certify teachers who meet those standards, and to advance other education reforms for the purpose of improving student learning in American schools." In response to a request from the U.S. Congress, the National Research Council developed a framework for evaluating programs that award advanced-level teacher certification and applied that framework in an evaluation of the impacts of the NBPTS. Specifically, this book addresses the impacts on students, teachers, and the educational system in this country. Assessing Accomplished Teaching finds that teachers who earn board certification are more effective at improving their students' achievement than other teachers, but school systems vary greatly in the extent to which they recognize and make use of board-certified teachers. Many of the questions on the evaluation framework could not be answered because the data have not been collected, and the report makes recommendations for the kinds of research that are needed to fully evaluate the impacts of board certification by the NBPTS.
Keywords: Education

Assessing the Role of K-12 Academic Standards in States: Workshop Summary - National Research Council (The National Academies Press, 2008)
Every state in the United States, the District of Columbia, and the Department of Defense Education Activity now has its own academic standards, at least in core subjects. These documents vary in their structure, level of specificity, and other characteristics. Professional societies have also developed standards, in mathematics, English language arts, science, social studies, civics, foreign languages, and other academic subjects, and many states have drawn on these as they prepared their own standards documents. Other organizations have also offered standards and benchmarks. For example, the Mid-continent Research for Education and Learning (McREL) offers standards developed with the goal of applying a consistent structure and degree of rigor and specificity to standards in diverse subjects. This abundance of standards reflects a vigorous response to the call for high standards articulated in the National Commission on Excellence in Education's 1983 report A Nation at Risk, and it also poses a variety of questions for educators, policy makers, and the public. What role are these standards playing? What are the strengths and weaknesses of the reform efforts that have been anchored by these standards? How are these standards applied, and how might standards-based reforms be improved? Would a move toward national standards in core academic subjects lead to improved instruction and learning? Would it be feasible? The committee identified three components to the charge for the first workshop: a review of the policy and research context in which current standards-based reform efforts are operating, a consideration of how the costs of standards and accountability systems might be calculated, and an analysis of similarities and differences among states' content and performance standards. Assessing the Role of K-12 Academic Standards in States: Workshop Summary summarizes this workshop and the committee's recommendations.
Keywords: Education

Protecting Individual Privacy in the Struggle Against Terrorists: A Framework for Program Assessment - National Research Council (The National Academies Press, 2008)
All U.S. agencies with counterterrorism programs that collect or "mine" personal data -- such as phone records or Web sites visited -- should be required to evaluate the programs' effectiveness, lawfulness, and impacts on privacy. A framework is offered that agencies can use to evaluate such information-based programs, both classified and unclassified. The book urges Congress to re-examine existing privacy law to assess how privacy can be protected in current and future programs and recommends that any individuals harmed by violations of privacy be given a meaningful form of redress. Two specific technologies are examined: data mining and behavioral surveillance. Regarding data mining, the book concludes that although these methods have been useful in the private sector for spotting consumer fraud, they are less helpful for counterterrorism because so little is known about what patterns indicate terrorist activity. Regarding behavioral surveillance in a counterterrorist context, the book concludes that although research and development on certain aspects of this topic are warranted, there is no scientific consensus on whether these techniques are ready for operational use at all in counterterrorism.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Conflict and Security Issues; Surveys and Statistics

Science Professionals: Master's Education for a Competitive World - National Research Council (The National Academies Press, 2008)
What are employer needs for staff trained in the natural sciences at the master's degree level? How do master's level professionals in the natural sciences contribute in the workplace? How do master's programs meet or support educational and career goals? Science Professionals: Master's Education for a Competitive World examines the answers to these and other questions regarding the role of master's education in the natural sciences. The book also focuses on student characteristics and what can be learned from efforts underway to enhance the master's in the natural sciences, particularly as a professional degree. This book is a critical tool for Congress, the federal agencies charged with carrying out the America COMPETES Act, and educational and science policy makers at the state level. Additionally, anyone with a stake in the development of professional science education (four year institutions of higher education, students, faculty, and employers) will find this book useful.
Keywords: Education; Industry and Labor

Martha Muse Prize for Science and Policy in Antarctica: An International Polar Year Legacy - National Research Council (The National Academies Press, 2008)
International Polar Year (IPY) 2007--2008 is an intense, coordinated field campaign of polar observations, research, and analysis. It is one of the largest collaborative science programs ever attempted, involving more than 200 projects and people from more than 60 nations. In honor of its long-time leader, Ms. Martha Twitchell Muse, and to provide a lasting legacy of IPY, the Tinker Foundation is establishing an annual, prestigious prize: the Martha Muse IPY Prize for Science and Policy in Antarctica This $100,000 unrestricted prize will be awarded following a nominations process similar to that of the National Medal of Science, meaning that people are nominated by others in the community. The goal is to provide recognition of the individual's outstanding and important work and to call attention to the importance of understanding Antarctica in this time of global climate change. This book outlines the strategy and steps necessary to take the Martha Muse Prize from concept to implementation. It describes the prize's purpose and nature, the system that could be used to announce the prize and collect nominations, potential procedures to be used by the Selection Committee, and possible post-award activities.
Keywords: Environment and Environmental Studies

Space Studies Board Annual Report 2007 (The National Academies Press, 2008)
Keywords: Space and Aeronautics

Understanding Crime Trends: Workshop Report - National Research Council (The National Academies Press, 2008)
Changes over time in the levels and patterns of crime have significant consequences that affect not only the criminal justice system but also other critical policy sectors. Yet compared with such areas as health status, housing, and employment, the nation lacks timely information and comprehensive research on crime trends. Descriptive information and explanatory research on crime trends across the nation that are not only accurate, but also timely, are pressing needs in the nation's crime-control efforts. In April 2007, the National Research Council held a two-day workshop to address key substantive and methodological issues underlying the study of crime trends and to lay the groundwork for a proposed multiyear NRC panel study of these issues. Six papers were commissioned from leading researchers and discussed at the workshop by experts in sociology, criminology, law, economics, and statistics. The authors revised their papers based on the discussants' comments, and the papers were then reviewed again externally. The six final workshop papers are the basis of this volume, which represents some of the most serious thinking and research on crime trends currently available.
Keywords: Behavioral and Social Sciences

Design Considerations for Evaluating the Impact of PEPFAR: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Design Considerations for Evaluating the Impact of PEPFAR is the summary of a 2-day workshop on methodological, policy, and practical design considerations for a future evaluation of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) interventions carried out under the President's Emergency Plan for AIDS Relief (PEPFAR), which was convened by the Institute of Medicine (IOM) on April 30 and May 1, 2007. Participants at the workshop included staff of the U.S. Congress; PEPFAR officials and implementers; major multilateral organizations such as The Global Fund to Fight AIDS, Malaria, and Tuberculosis (The Global Fund), the Joint United Nations Programme on HIV/AIDS (UNAIDS), and the World Bank; representatives from international nongovernmental organizations; experienced evaluation experts; and representatives of partner countries, particularly the PEPFAR focus countries. The workshop represented a final element of the work of the congressionally mandated IOM Committee for the Evaluation of PEPFAR Implementation, which published a report of its findings in 2007 evaluating the first 2 years of implementation, but could not address longer term impact evaluation questions.
Keywords: Health and Medicine

Agriculture, Forestry, and Fishing Research at NIOSH: Reviews of Research Programs of the National Institute for Occupational Safety and Health - National Research Council; Institute of Medicine (The National Academies Press, 2008)
The agriculture, forestry, and fishing sectors are the cornerstone of industries that produce food, fiber, and biofuel. The National Institute for Occupational Safety and Health (NIOSH) conducts research in order to improve worker safety and health in these sectors. This National Research Council book reviews the NIOSH Agriculture, Forestry, and Fishing Program to evaluate the 1) relevance of its work to improvements in occupational safety and health and 2) the impact of research in reducing workplace illnesses and injuries. The assessment reveals that the program has made meaningful contributions to improving worker safety and health in these fields. To enhance the relevance and impact of its work and fulfill its mission, the NIOSH Agriculture, Forestry, and Fishing Program should provide national leadership, coordination of research, and activities to transfer findings, technologies, and information into practice. The program will also benefit from establishing strategic goals and implementing a comprehensive surveillance system in order to better identify and track worker populations at risk.
Keywords: Agriculture; Earth Sciences; Health and Medicine

Space Science and the International Traffic in Arms Regulations: Summary of a Workshop - National Research Council (The National Academies Press, 2008)
ITAR, which controls defense trade, includes the U.S. Munitions List (USML) which specifies categories of defense articles and services covered by the regulations. In 1999, space satellites were added to the USML. In 2002 ITAR was amended to exclude U.S. universities from having to obtain ITAR licenses when performing fundamental research involving foreign countries and/or persons. Despite this provision, there remains considerable uncertainty among university researchers about whether the regulations apply to their research leading to a rather conservative interpretation of the regulations and the imposition of burdens that might not be necessary. To explore this concern, NASA asked the NRC to organize a workshop of all stakeholders on the implications of ITAR for space science. This book presents a summary of the workshop discussions including those on perspectives on recent developments and implementation of ITAR; overarching issues; problems arising from ITAR's implementation; and opportunities for near-term actions and improvements.
Keywords: Conflict and Security Issues; Space and Aeronautics